Gamification Based Learning Media for Fostering Entrepreneurial Disposition in Early Childhood - Windarsih, Chandra Asri; Rizkita , Diantifani; Hadian, Mohamad Heri (JURNAL PENDIDIKAN USIA DINI, 2026)
Instilling an entrepreneurial mindset from an early age has not yet become a strong foundation for developing independent and adaptable generations. This study aimed to examine the effectiveness of gamification-based learning media in fostering entrepreneurial attitudes among young children. Using a modified Borg & Gall Research and Development method with seven stages—needs analysis, design, product creation, expert validation, revision, trials, and impact testing—data were collected through behavioural observation, interviews, and expert-validated questionnaires. Trials were conducted in three early childhood centres involving 60 children aged 5–6 years. Results showed the gamification media was highly feasible, achieving expert validation scores above 90%, and significantly improved children’s entrepreneurial traits such as independence (p = 0.002), initiative (p = 0.005), and problem-solving skills (p = 0.001). Gamification increased learning motivation and encouraged positive social collaboration. In conclusion, interactive, contextually designed gamification media effectively build early entrepreneurial foundations. This research contributes to the integration of gamification and entrepreneurship education within contextual design frameworks, offering practical implications for early childhood education and introducing digital innovations that promote economic literacy from an early age.